(S)-3-[(S)-5-(4-Fluorophenyl)-5-hydroxypentanoyl]-4-phenyloxazolidin-2-one 0.67-hydrate - Xiao-Guang Wang; Qing-Shuang Ma; Bin Sun; Lei Xu; Feng-Tao Zhan; Geng-Xiu Zheng (IUCrData, 2017)
The asymmetric unit of the title compound, 3C20H20FNO4·2H2O, consists of three (S)-3-[(S)-5-(4-fluorophenyl)-5-hydroxypentanoyl]-4-phenyloxazolidin-2-one molecules and two solvent water molecules. The carbonyl groups of the oxazolidin-2-one and hydroxypentanoyl units are oriented anti to one another in each molecule. In the crystal, O—H...O, C—H...O and C—H...F hydrogen bonds link the molecules into a three-dimensional supramolecular architecture with the organic molecules linked by water molecules and stacked along the b-axis direction.